PEMETAAN TREN PENELITIAN SHARIA COMPLIANCE PADA LEMBAGA KEUANGAN SYARIAH: STUDI BIBLIOMETRIK VOSVIEWER - Fauziyah, Nurul; Wulandari, Anggiani Sri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the development trend of research related to sharia compliance in Islamic financial institutions during the period from 2014 to 2024. A search was conducted through Google Scholar in Perish/Harzing with the keyword